Intergenerational differences of school leaders' reflective practice and ethical dilemma resolution - Medallon, Kim Gerald G.; Buenviaje, Jerome T.; Patriarca, Marian Christine V.; Javaniar, Joel C.; Muega, Maricris Acido; Valenzuela, Ethel Agnes Pascua (Quezon City College of Education, University of the Philippines Diliman, 2023)
Reflective practice and ethical dilemma resolution are potent that school leaders tap to attain set organizational goals, as well as to improve the welfare of stakeholders. Currently, there is a dearth of literature on the process taken by novice school leaders to engage in these leadership tools, as well as identifying enablers that facilitate them and ensure transition to quality practices evident in seasoned school leaders. A qualitative approach, through a case study design, was utilized to come up with a framework describing the interplay of these leadership tools and highlighting intergenerational differences between novice and seasoned school leaders. Six novice and seasoned school leaders from the National Capital Region and Region IV-A participated in this study through the key informant interviews. Thematic analysis was used in analyzing the results. Results of the study showed a difference in the quality and focus between these two sets of leaders when engaging in reflective practice and ethical dilemma resolution. Personal and contextual enablers, along with the overall process, were generally different. Enablers in the transition toward an improved set of practices shared some similarities and enriched the current set of enablers for seasoned school leaders. These two concepts are closely intertwined with each other contributing to a more comprehensive, effective, and sharpened performance of leadership tasks. The identified enablers and process may pave the way for more relevant leadership preparation and development programs and policies that can reap benefits for the organization and its stakeholders when these two leadership tools are maximized.
Thesis
Includes bibliographical references (251-267 leaves)
Keywords: School management and organization -- Philippines -- National Capital Region; School management and organization -- Philippines -- Calabarzon; School administrators -- Philippines -- National Capital Region -- Attitudes; School administrators -- Philippines -- Calabarzon. -- Attitudes; Ethical problems